1988
DOI: 10.1002/cjce.5450660218
|View full text |Cite
|
Sign up to set email alerts
|

The importance of temperature rise time in pyrolysis kinetic studies

Abstract: The measurement of the kinetics of fast chemical reactions, such as hydrocarbon pyrolysis, is often hampered by limitations of the experimental reactor. To overcome problems in getting to reaction temperature, a micro‐reactor system has been developed with temperature rise times (TRT) in the millisecond range. Data is presented for the dynamic response of a Curie Point pyrolyser along with a computer simulation of how the gas‐filled micro‐reactor would respond. The importance of temperature rise time is clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The temperature rise time, that is, the time for reaching a reactor temperature, from ambient temperature, was also recognized as a key requirement in ultrapyrolysis kinetic studies. [ 46 ] The importance of rapid quenching also reverberated in modelling studies of cooling of product gases in the quench line exchangers downstream of ethane pyrolysis and propane pyrolysis reactors. [ 47,48 ] Both of these studies revealed that quenching of product gases could be achieved in less than 10–15 ms.…”
Section: Contributions To Topics In Chemical Engineeringmentioning
confidence: 99%
“…The temperature rise time, that is, the time for reaching a reactor temperature, from ambient temperature, was also recognized as a key requirement in ultrapyrolysis kinetic studies. [ 46 ] The importance of rapid quenching also reverberated in modelling studies of cooling of product gases in the quench line exchangers downstream of ethane pyrolysis and propane pyrolysis reactors. [ 47,48 ] Both of these studies revealed that quenching of product gases could be achieved in less than 10–15 ms.…”
Section: Contributions To Topics In Chemical Engineeringmentioning
confidence: 99%
“…The primary technical challenge in using commercial reactors is to make accurate measurements of the actual temperature of biomass sample. Knowing the time-temperature history within the sample is critical to assessing the chemical modeling of biomass fast pyrolysis [31]. The determination of the actual heating rates of the biomass sample remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous-flow tubular reactors have been used by previous researchers to study pyrolysis of n -alkanes at elevated temperatures, but this type of reactor does not give an isothermal temperature profile or a very fast temperature rise to desired temperatures . The use of a Curie point pyrolyzer to overcome the significant temperature profile in an externally heated tubular reactor was demonstrated for propane and n -hexadecane 576–842 °C . Other techniques, such as laser heating give faster heating but lack the ability to correctly determine, control, and maintain a final temperature.…”
Section: Introductionmentioning
confidence: 99%